This preview shows page 1. Sign up to view the full content.
From equation 9.5.8, with
( )
11
1
3
ˆˆ
ee
e
ωω
ω
=+ =
+
D
ˆ
G
G
:
()
2
1
2
cos45
Ω=
−
=
D
From equation 9.6.12 …
( )
1
22
2
2121c
o
s
4
5
5
φω
=+
−
=
D
±
9.15
2 2
33
ˆˆˆ
Nc ce e e
=−
+
+
G
G
Say the 3 axis is the symmetry axis,
3
s
I
I
=
,
12
I
II
=
=
For the third component of equations 9.3.5 …
0
s
cI
−
±
G
N
G
α
3
1
3
3
s
c
I
= −
±
3
3
ln
s
c
t
I
D
s
ct
I
e
−
=
D
2
For the first two components of equations
9.3.5 …
( )
2
3
s
I
I
−
−
±
, and
( )
1
3
s
I
I
−= +
−
±
Rearranging terms and multiplying by
1
and
2
respectively …
2
1
12 3
0
s
c
I
ωωω
++
−
=
±
2
2
123
0
s
c
I
+−
−
=
±
Adding,
1
2
0
c
I
++ +=
±±
dc
dt
I
+=
−
+
2
ln
c
t
I
+
+
D
2
ct
I
e
−
+=+
D
ct
I
e
D
1
2
3
tan
tan
This is the end of the preview. Sign up
to
access the rest of the document.
This note was uploaded on 01/06/2012 for the course PHYSICS 4360C taught by Professor Johnanderson during the Fall '11 term at UNF.
 Fall '11
 JohnAnderson
 Work

Click to edit the document details